2016
DOI: 10.1002/ece3.2565
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation resource partitioning of Lesser Frigatebirds and the influence of environmental context

Abstract: Conspecific individuals inhabiting nearby breeding colonies are expected to compete strongly for food resources owing to the constraints imposed by shared morphology, physiology, and behavior on foraging strategy. Consequently, colony‐specific foraging patterns that effectively partition the available resources may be displayed. This study aimed to determine whether intraspecific resource partitioning occurs in two nearby colonies of Lesser Frigatebirds (Fregata ariel). A combination of stable isotope analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Tropicbird Phaethon and frigatebirdFregata species were grouped respectively (Table 1) to boost sample size and make family level models, acknowledging that foraging differences between species within these families have been observed (e.g. Mott et al 2016). Noddy Anous species were modelled as a family group (following evidence of foraging niche overlap; Surman & Wooller 2003, Shephard et al 2018, and large tern Thalasseusand Hydroprogne species were aggregated into a meta-family group for modelling.…”
Section: Tracking Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Tropicbird Phaethon and frigatebirdFregata species were grouped respectively (Table 1) to boost sample size and make family level models, acknowledging that foraging differences between species within these families have been observed (e.g. Mott et al 2016). Noddy Anous species were modelled as a family group (following evidence of foraging niche overlap; Surman & Wooller 2003, Shephard et al 2018, and large tern Thalasseusand Hydroprogne species were aggregated into a meta-family group for modelling.…”
Section: Tracking Datamentioning
confidence: 99%
“…We also manually removed trips that spent too much time away from the colony, indicating breeding failure. Upper trip duration limits were set at five days for boobies (Mendez et al 2017), 12 days for frigatebirds (Mott et al 2016) and tropicbirds, 14 days for wedge-tailed shearwater long trips (McDuie et al 2015) and sooty terns (Neumann et al 2018), three days for wedge-tailed shearwater short trips (Weimerskirch et al 2020) and two days for noddies and terns (from inspection of data).…”
Section: Tracking Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable isotopes allow tracking of diet over long time scales due to archived specimens and may provide insights on important trophic changes 52 . These changes may occur over very long periods, hundreds of years or decades 49 , 53 , or shorter periods, such as seasons or consecutive years 30 , 54 , 55 . Thus, isotope measurements in historical samples link population trends with diet shifts across time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wakefield et al (2013) showed that 12 colonies of northern gannets (Morus bassanus), distributed around the British shoreline, forage in mutually exclusive areas, including six colonies located very close to each other. Other studies reported spatial partitioning between neighboring colonies in a wide range of systems, most commonly in breeding colonies of marine birds (Ainley et al, 2004;Ceia et al, 2015;Corman et al, 2016;Mott et al, 2016;Sánchez et al, 2018;Bolton et al, 2019;Ito et al, 2020;Jessopp et al, 2020), but also in other birds (Cecere et al, 2018), ants (Gordon and Kulig, 1996;Adler and Gordon, 2003;Richardson et al, 2017) and a few other taxa (Ellis et al, 2009;Papastamatiou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%